La percezione del corpo in scena e lo spettatore: Un approccio neuro-scientifico - Zardi, Andrea (Mimesis Journal, 2018)
Dance has investigated the processes of construction of the body also in a cultural sense and the meanings they assume inside theatre: it did it the as if, in direct correspondence of meanings, but been subject to a work of imagination and elaboration of images. With the birth of performance the role of meaning and the concreteness of the sign of the body gets to a level of urgency, directly projected on the spectator. The person attending doesn’t have to look for a meaning to give to a gesture anymore, but it is his reaction and behaviour to become itself the object of the performance. We observe a process of multiplication of the levels of reference of what happens on the scene, both on a human and relational point of view and in the perspective of the contents: in this contest of research we decided to start from an experimental analysis which could take into consideration the conquers of neuroscience concerning recep- tion, to consider the critical developments and to look for its roots inside the choreographical practice. Briefly, we will explain which methodologic approaches have taken place, starting from literature and the aims from a not only scientific point of view, but also in a in-depth analysis of the Dance Studies. We will try to explain how the brain is able to perceive beauty and empathize with the dancer: how the “dancing spectator” could feel the performer’s body as his own.